1980
DOI: 10.1111/j.1365-2125.1980.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of atenolol in patients with terminal renal failure and influence of haemodialysis.

Abstract: 1 The pharmacokinetics of atenolol, after 200 mg orally, were studied in 18 patients with terminal renal insufficiency (creatinine clearance less than 5 ml/min), of whom twelve were being treated by chronic dialysis. 2 The peak plasma level, 1.59 +/‐ 0.43 mg/l, was reached in 4.7 +/‐ 2.1 h. 3 Without dialysis treatment, the apparent plasma half‐ life of atenolol was greatly increased (73.4 +/‐ 28.8 /). During dialysis, it dropped to 7.5 +/‐ 3.7 h but returned to 51.2 +/‐ 17.3 h after dialysis. The plasma ateno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…After haemodialysis, in patients undergoing regular dialysis treatment, the plasma half-life was slightly shorter than in patients with terminal renal failure but that have not yet been dialyzed (CLcr between 4 and 10 ml/min). We have also observed this phenomenon with atenolol, a drug in which the plasma half-life after dialysis (51.2 + 17.3 h) is shorter than that in patients before the first haemodialysis treatment (73.4 ± 28.8 h) (Flouvat et al, 1980). In our patients, the apparent tinidazole volume of distribution (0.64 ± 0.03 1/kg) was equivalent to extra and intracellular water volume (0.55-0.65 1/kg) (Rowland & Tozer, 1980).…”
Section: Discussionmentioning
confidence: 64%
“…After haemodialysis, in patients undergoing regular dialysis treatment, the plasma half-life was slightly shorter than in patients with terminal renal failure but that have not yet been dialyzed (CLcr between 4 and 10 ml/min). We have also observed this phenomenon with atenolol, a drug in which the plasma half-life after dialysis (51.2 + 17.3 h) is shorter than that in patients before the first haemodialysis treatment (73.4 ± 28.8 h) (Flouvat et al, 1980). In our patients, the apparent tinidazole volume of distribution (0.64 ± 0.03 1/kg) was equivalent to extra and intracellular water volume (0.55-0.65 1/kg) (Rowland & Tozer, 1980).…”
Section: Discussionmentioning
confidence: 64%
“…The half-life of atenolol has been shown to be prolonged in patients with renal impairment and to correlate inversely with creatinine clearance (McAinsh et al, 1980). Previous studies have shown that patients having creatinine clearance less than 10 mlmin would be expected to have atenolol half-lives of between 35 and 100 h. In contrast in patients with chronic renal failure who undergo haemodialysis the elimination of atenolol during the period of dialysis is more rapid and the measured half-lives approximate to those observed in normal volunteers with normal renal function, suggesting that atenolol is cleared across the dialysis membrane (Flouvat et al, 1980). CAPD is increasingly used in the U.K. as therapy for chronic renal failure but the clearance of atenolol into the peritoneum has not been previously studied.…”
Section: Discussionmentioning
confidence: 92%
“…Massive continued absorption is possible, but unlikely based on removal of substantial pill fragments and declining concentrations. Plasma atenolol concentrations have also been observed to increase post-dialysis reflecting redistribution from the tissue in HD patients [8,21]. Tissue may therefore be a large reservoir, especially after overdose.…”
Section: Discussionmentioning
confidence: 95%